Gastric Cancer – From Aetiology to Management: Differences Between the East and the West. Issue 8 (August 2019) - Chan, W.L.; Lam, K.O.; Lee, V.H.F.; Davidson, M.; So, T.H.; Li, J.S.; Chau, I.; Kwong, D.L.W.
Abstract: Gastric cancers are highly prevalent in both the East and the West, although they differ in aetiology and prognostic outcome. Management of gastric cancer from screening to definitive treatment varies substantially between Eastern and Western countries and regions, owing to numerous factors, including government incentives to carry out population-wide screening programmes to detect early disease, differences in clinical and biological tumour behaviours and responsiveness to treatment, patient accessibility to effective treatment, etc. This review highlights and contrasts the differences in tumour aetiology and histology, as well as the management approaches between the East and the West, which gives important insights and inspirations on future international multicentre research collaboration to combat this dreadful malignancy.